2018
DOI: 10.1088/1755-1315/102/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Bacillus thuringiensis Berl. from soil and screening test its toxicity on insects of Lepidoptera order

Abstract: Abstract.Bacillus thuringiensis is a gram-positive bacterium that produces crystal proteins toxic (ᴕ-endotoxin) specific to the target insect, but is not toxic to humans and non-target organisms. This study aims to explore the origin of the soil bacterium B. thuringiensis subdistrict Sekayu, Banyuasin, South Sumatra and toxicity to larvae of lepidoptera. Fifty soil samples were taken from Musi Banyuasin District, namely 15 from Kayuare strip 2, 20 from Kayuare and 15 from Lumpatan. Isolation, characterization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
2
0
0
Order By: Relevance
“…and Thauera sp., stopped feeding, turned black and became sluggish before death. Similar symptoms have earlier been reported in P. xylostella and S. litura larvae due to infection of B. thuringiensis , Lysinibacillus sphaericus , Klebsiella pneumonia and Pseudomonas paralactis (Astuti et al, 2018; Bravo et al, 2017; Devi et al, 2022). Pathogenicity of Shewanella sp.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…and Thauera sp., stopped feeding, turned black and became sluggish before death. Similar symptoms have earlier been reported in P. xylostella and S. litura larvae due to infection of B. thuringiensis , Lysinibacillus sphaericus , Klebsiella pneumonia and Pseudomonas paralactis (Astuti et al, 2018; Bravo et al, 2017; Devi et al, 2022). Pathogenicity of Shewanella sp.…”
Section: Discussionsupporting
confidence: 81%
“…and Thauera sp., stopped feeding, turned black and became sluggish before death. Similar symptoms have earlier been reported in P. xylostella and S. litura larvae due to infection of B. thuringiensis, Lysinibacillus sphaericus, Klebsiella pneumonia and Pseudomonas paralactis (Astuti et al, 2018;Bravo et al, 2017;Devi et al, 2022) Andrejko & Mizerska-Dudka, 2012;Maciel-Vergara et al, 2018;Matsumoto, 2004;Ng et al, 2015;OztasGulmus & Gormez, 2020;Tarhriz et al, 2011;Vallet-Gely et al, 2008). These hydrolytic enzymes are known to aid in disrupting the cuticle, peritrophic matrix and hydrolyzing their lipoproteins, fats and other molecules present in the integument, causing its degradation (Lopes et al, 2021).…”
Section: Discussionsupporting
confidence: 63%
“…The protein toxin attached to the receptor protein located on the surface of epithelial cells of the intestine destroys the structure and function of epithelial cells in the insect's digestive tract, resulting in lysis and decreased appetite, and insect death (Schünemann et al 2014). Bacillus thuringiensis at a density of 106/mL spore density can result in high mortality on target insects because B. thuringiensis has high virulence (Afriani et al 2017;Astuti 2017;Ghazwan et al 2017;Pujiastuti et al 2018;Sayid et al 2020). The results of the deadline of insect mortality (LT50) applied by bacterial isolates of B. thuringiensis showed that the ability to kill insects of each isolate tested varied between an average of 2.94 to 7.43 days.…”
Section: Bioassay Of Bacillus Thuringiensis Against Spodoptera Lituramentioning
confidence: 99%